High-frequency Doppler ultrasound flowmeter - NOWICKI, A.; SECOMSKI, W.; KARŁOWICZ, P.; ŁYPACEWICZ, G. (Archives of Acoustics, 1994)
This paper discusses a new Doppler device for measuring blood flow in small vessels. The ultrasound frequency applied is 20M Hz. Two different ultrasound probes were designed with transducer diameters of 0.9 mm and 1.6 mm. The transducers were located at the point of a catheter. As measured at 1.5 mm depth, the lateral resolutions were 1 mm and 1.7 mm, respectively. The flowmeter is very sensitive. Compared with standard flowmeters (from 2 to 8 MHz), signals from subcutaneous vessels are greater by 10-20 dB.